URGENSI PERUBAHAN DEFINISI PEMBAJAKAN PADA REZIM PELINDUNGAN HAK CIPTA DIGITAL DI INDONESIA - Kamila, Deasy; Permata, Rika Ratna; Wijaya, Viona (Legislatif, 2024)
Technological developments have brought changes in various sectors of life, including copyright protection. The presence of subscription-based streaming platforms has changed the way individuals enjoy digital creative works. Along with the rapid pace of technological development, a new phenomenon in digital copyright infringement activities has emerged, namely the illegal sale of subscription-based streaming platform accounts. This research aims to examine the need for revising provisions regarding digital copyright protection, especially the definition of piracy. The research method used is normative legal research through offline and online document studies, using qualitative descriptive data analysis methods to obtain explanatory conclusions. Based on the research results, it was found that the current legal framework for protecting digital copyright cannot protect creators and copyright license holders from the illegal sale of streaming accounts. The access structure in subscription-based streaming platforms has substantially changed how copyrighted content is enjoyed and how piracy can be conducted. Based on this, the author concludes that it is necessary to change the definition of piracy within the scope of copyright protection by adding the element of 'illegal access' so that copyright protection in the digital era can be carried out optimally.